Changes in some morphological characteristics and motor skills between female volleyball players and female handball players - Mimoza Shkodra; Nazim Myrtaj; Arben Bislimi (Kazimierz Wielki University, 2019)
The population from which the sample is taken for this paper is defined as the population of senior culminating athletes in the game of volleyball and handball, in the Kosovo superleague. The sample for the purposes of this research will include 100 female athletes, respectively, 50 female volleyball players and 50 female habdball players.The variables that are applied in this research are anthropometric and motor variables.8 anthropometric variables and7motor variables were applied. The results obtained from the collection of information and their processing, shows that the gained differencies between female volleyball players and female handball players in the motor variables of the explosive and situational force, indicate that during the preparatory phase in the volleyball game, it was expercised in the right way in the raising of these motor skills, while it was not given enough in the importance to the expercises of the explosive force of lower extremities.